Asbāb al-Wurūd dalam Dinamika Kajian Hadis di Indonesia (2011–2023): Pemetaan Systematic Literature Review - Sadali, Ahmad David Imron; Baehaki, Ahmad; Fadlurahman, M. Hammam; Mubarak, M. Luthfi (Journal of Hadith Studies, 2023)
This study aims to analyze the trends and methodological tendencies of asbāb al-wurūd research in Indonesia between 2011 and 2024 using a Systematic Literature Review (SLR) approach. A total of 20 academic publications were systematically examined to map the trajectory and quality of this growing discourse. Findings indicate that the historical-contextual approach dominates, positioning asbāb al-wurūd as a crucial framework for understanding the relevance of hadith in contemporary socio-religious contexts. Rather than serving solely as a supporting tool, asbāb al-wurūd has emerged as an interpretive method addressing issues such as education, gender justice, and reinterpretation of controversial narrations. However, the research remains largely repetitive and descriptive, lacking theoretical and methodological innovation. Therefore, this study recommends interdisciplinary and reflective methodological expansion within asbāb al-wurūd research and suggests extending SLR applications to other hadith-related fields to support epistemological renewal.